Video Integrity Verification and GOP Size Estimation via Generalized Variation of Prediction Footprint - David Vázquez-Padín; Marco Fontani; Dasara Shullani; Fernando Pérez-González; Alessandro Piva; Mauro Barni (IEEE Transactions on Information Forensics and Security, 2020)
The Variation of Prediction Footprint (VPF), formerly used in video forensics for double compression detection and GOP size estimation, is comprehensively investigated to improve its acquisition capabilities and extend its use to video sequences that contain bi-directional frames (B-frames). By relying on a universal rate-distortion analysis applied to a generic double compression scheme, we first explain the rationale behind the presence of the VPF in double compressed videos and then justify the need of exploiting a new source of information such as the motion vectors, to enhance the VPF acquisition process. Finally, we describe the shifted VPF induced by the presence of B-frames and detail how to compensate the shift to avoid misguided GOP size estimations. The experimental results show that the proposed Generalized VPF (G-VPF) technique outperforms the state of the art, not only in terms of double compression detection and GOP size estimation, but also in reducing computational time.
Keywords: B-frames; double compression detection; GOP size estimation; rate distortion optimization; video forensics

Localization of Forgeries in MPEG-2 Video through GOP Size and DQ analysis - Daniele Labartino; Tiziano Bianchi; Alessia De Rosa; Marco Fontani; David Vázquez-Padín; Alessandro Piva; Mauro Barni (IEEE International Workshop on Multimedia Signal Processing (MMSP), 2013)
This work addresses forgery localization in MPEG-2 compressed videos. The proposed method is based on the analysis of Double Quantization (DQ) traces in frames that were encoded twice as intra (i.e., I-frames).  Employing a state-of-the-art method, such frames are located in the video under analysis by estimating the size of the Group Of Pictures (GOP) that was used in the first compression; then, the DQ analysis is devised for the MPEG-2 encoding scheme and applied to frames that were intra-coded in both the first and second compression. In such a way, regions that were manipulated between the two encodings are detected. Compared to existing methods based on double quantization analysis, the proposed scheme makes forgery localization possible on a wider range of settings.

Near optimal detection of quantized signals and application to JPEG forensics - Tiziano Bianchi; Alessandro Piva; Fernando Pérez-González (2013 IEEE International Workshop on Information Forensics and Security (WIFS), 2013)

Detection of video double encoding with GOP size estimation - David Vázquez-Padín; Marco Fontani; Tiziano Bianchi; Pedro Comesaña; Alessandro Piva; Mauro Barni (IEEE International Workshop on Information Forensics and Security (WIFS), 2012)
Video forensics is an emerging discipline, that aims at inferring information about the processing history undergone by a digital video in a blind fashion. In this work we introduce a new forensic footprint and, based on it, propose a method for detecting whether a video has been encoded twice; if this is the case, we also estimate the size of the Group Of Pictures (GOP) employed during the first encoding. As shown in the experiments, the footprint proves to be very robust even in realistic settings (i.e., when encoding is carried out using typical compression rates), that are rarely addressed by existing techniques.